Setting the tone for the day: Cortisol awakening response proactively modulates fronto-limbic circuitry for emotion processing - Changming Chen; Bingsen Xiong; Wenlong Tan; Yanqiu Tian; Shouwen Zhang; Jianhui Wu; Peng Song; Shaozheng Qin (NeuroImage)
The cortisol awakening response (CAR) has been linked to a variety of emotion-related psychiatric conditions and is proposed to prepare the brain for upcoming stress and challenges. Yet, the underlying neurobiological mechanisms of such proactive effects on emotional processing remain elusive. In the current double-blinded, pharmacologically-manipulated study, 36 male adults (DXM group) received cortisol-repressive dexamethasone on the previous night, then performed the Emotional Face Matching Task (EFMT) during fMRI scanning the next afternoon. Relative to the placebo group (31 male adults), the DXM group exhibited lower accuracy in the emotion matching condition, but not in the sensorimotor control condition. Psychophysiological interaction (PPI) analyses revealed significant task-by-group interaction involving the right and left amygdala, but not the medial orbitofrontal cortex (MOFC) or hippocampus. Specifically, the DXM group exhibited stronger functional connectivity between the right amygdala and left dorsolateral prefrontal cortex (lDLPFC) during emotion condition but reduced connectivity in the same network during control condition, as compared to the placebo group. Meanwhile, the DXM group exhibited weaker left amygdala–right posterior middle temporal gyrus (rMTG) connectivity than the placebo group during control condition, but there was no group effect in the connectivity during emotion condition. These results indicate that the CAR proactively modulates fronto-limbic functional organization for emotion processing in male adults. Our findings support a causal link between CAR and its proactive effects on emotional processing, and suggest a model of CAR-mediated brain preparedness where CAR sets a tonic tone for the upcoming day to actively regulate neuroendocrinological responses to emotionally charged stimuli on a moment-to-moment basis.